El viaje de los sentidos en los jardines de Mogador - Tudoras, Laura Eugenia (Revista de Filología Románica, 2006)
This article proposes a symbolic reading of the sensory real and imaginary travels to the city of the desire: Mogador. Likewise it presents a relation of metaphorical analogies between concepts as: space-garden-city-woman body-desire, in a literary representative text of the Mexican current narrative: The Secret Gardens of Mogador.